2017
DOI: 10.3892/mmr.2017.7966
|View full text |Cite
|
Sign up to set email alerts
|

Sparstolonin B prevents lumbar intervertebral disc degeneration through toll like receptor 4, NADPH oxidase activation and the protein kinase B signaling pathway

Abstract: Intervertebral disc degeneration (IVDD) is the most common pathogeny of lumbago. It is the pathological basis for a series of spinal degenerative diseases. For a long time, the diagnosis and treatment of lumbago have rendered difficult, since the pathogeny has not been identified. Therefore, the present study aimed to investigate the protective effect of Sparstolonin B in preventing lumbar intervertebral disc degeneration, and explored its potential mechanism in rats. Firstly, Sparstolonin B effectively reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Therefore, the present study suggested that the NF-κB signaling pathway regulated the expression of cytokines via p53. A previous study reported that sparstolonin B prevents lumbar IDD-induced inflammation, oxidative stress and apoptosis via the toll-like receptor 4/MyD88/NF-κB signaling pathway ( 52 ). Furthermore, small ubiquitin like modifier 2 gene silencing inhibits nucleus pulposus cell apoptosis and senescence in a rat model of IDD by downregulating the p53 signaling pathway ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study suggested that the NF-κB signaling pathway regulated the expression of cytokines via p53. A previous study reported that sparstolonin B prevents lumbar IDD-induced inflammation, oxidative stress and apoptosis via the toll-like receptor 4/MyD88/NF-κB signaling pathway ( 52 ). Furthermore, small ubiquitin like modifier 2 gene silencing inhibits nucleus pulposus cell apoptosis and senescence in a rat model of IDD by downregulating the p53 signaling pathway ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…As TLR expression is elevated and the chondrocytes are strongly responsive to alarmins in scoliotic cartilage blocking their activity could potentially modify disease progression. To assess the effect of blocking TLR activation, two naturally derived compounds that prevent the recruitment of MyD88 to the TIR domain of TLRs, and thus TLR signalling, were used 31,41 . The antagonists did not significantly modulate gene expression in scoliotic chondrocytes challenged with biglycan (Figure 4A,B).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the effect of blocking TLR activation, two naturally derived compounds that prevent the recruitment of MyD88 to the TIR domain of TLRs, and thus TLR signalling, were used. 31,41 The antagonists did not significantly modulate gene expression in scoliotic chondrocytes challenged with biglycan ( Figure 4A,B).…”
Section: Sparstolonin B and O -Vanillin Reduced Alarmininduced Tlr mentioning
confidence: 93%
See 2 more Smart Citations